Understanding financial hardship and financial recovery among clients in supported accommodation services - Wendy M. M. Albers; Jaap van Weeghel; Diana P.K. Roeg (PLoS ONE, 2025)
Background Financial stability is essential for well-being, influencing health, housing, education, and social participation. Individuals with mental illness often face financial hardship, including debt, financial administration problems, and limited access to basic needs. Despite its importance, little research exists on factors supporting financial self-management for this group. This study explores financial hardship experiences, causes, and support mechanisms among clients in supported accommodation in the Netherlands. Methods Twenty-seven clients were recruited via staff of a large supported accommodation setting in the Netherlands, of which 22% received residential support and 48% received floating outreach. Semi-structured interviews were conducted, and thematic analysis was used to interpret participants’ lived experiences with financial problems. Results Participants identified several causes for their financial struggles, including psychological issues, impulsive spending, and a lack of financial literacy. Relationship problems (e.g., divorce) and limited social support also were mentioned to contribute to ongoing financial hardship. Budget coaches, professionals with expertise in debt management, offer personalized guidance and practical assistance with financial management, including creating budgets, managing expenses, and addressing debts. This support was highly valued by clients, helping them to organize their finances, manage expenses, reduce stress, and develop their financial literacy. Conclusions This study highlights the complex and multifaceted nature of financial difficulties experienced by clients in supported accommodation. Budget coaches, with their specialized knowledge of the target population and financial expertise, can play a crucial role in improving the financial situation of individuals with mental illness. The findings underscore the need for integrated support addressing both financial and mental health challenges to promote long-term independence and well-being for this vulnerable population in the Netherlands.